Perancangan Sistem Informasi Pelayanan Jasa Furniture Pada Perusahaan Perabot Ada Jaya Kota Jambi - Fitra Kebesa Miten; Sugeng Wibowo; Mutmainnah; Mukthar, Robby (LPPM STIKOM Dinamika Bangsa, 2025)
Service information systems have been widely used by developing companies and universities. Service information at the furniture company Ada Jaya Jambi City is currently still using a manual system, namely using an order receipt note making it difficult to search for data and takes a long time to print reports. . In this information system, it can make it easier for employees to process goods data, submit goods submissions and prepare the required reports, such as reports on admin data, customer data, data on types of goods, and transaction data. This information system uses XAMPP software as localhost, uses MySQL as data storage and processing and the programming language used is the PHP (Personal Home Page) programming language